2021
DOI: 10.2147/opto.s277786
|View full text |Cite
|
Sign up to set email alerts
|

Wearing Pattern and Awareness About Contact Lens Wear in Secondary School Students in Kuala Lumpur

Abstract: Purpose: To investigate the wearing pattern and awareness about contact lens care among secondary school students in Kuala Lumpur. Patients and Methods: This is a cross-sectional study using self-administered validated questionnaires. A total of 2500 questionnaires were distributed to secondary school students (aged 13 to 18 years) from 5 selected schools in Kuala Lumpur. Descriptive statistics were used to analyze the results. Results: A total of 987 completed questionnaires were returned and analyzed. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In agreement with previous studies, CL wearers were predominantly female. 12 , 19 Although findings from Saudi Arabia and India imply that the most common reason in females for choosing CLs is cosmetic purposes, 20 , 21 the majority of females in the present study wore CLs to correct refractive errors. Females were previously found to be less likely to follow the replacement schedule; 22 however, this outcome was not established in our study.…”
Section: Discussionmentioning
confidence: 61%
“…In agreement with previous studies, CL wearers were predominantly female. 12 , 19 Although findings from Saudi Arabia and India imply that the most common reason in females for choosing CLs is cosmetic purposes, 20 , 21 the majority of females in the present study wore CLs to correct refractive errors. Females were previously found to be less likely to follow the replacement schedule; 22 however, this outcome was not established in our study.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown varied reasons for CL usage [ 9 , 13 , 18 ]. In this study, only 23.8% of the participants used them for therapeutic purposes, whereas 50.6% indicated cosmetic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Spectacle correction is a cost-effective option [ 15 ] because it can be worn full-time, requires low maintenance, and has a low risk of complications. Contact lens correction has gained popularity among teenagers [ 16 ] as it is relatively inexpensive and easily accessible in Malaysia [ 17 ]. In contrast, patients must meet preoperative criteria for refractive surgery mode, and the procedure involves additional costs for postoperative follow-up.…”
Section: Introductionmentioning
confidence: 99%